1982
DOI: 10.1073/pnas.79.24.7896
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy by intravenous administration of conjugates of daunomycin with monoclonal and conventional anti-rat alpha-fetoprotein antibodies.

Abstract: Monoclonal antibodies to rat a-fetoprotein (AFP) were produced by hybridization of mouse myeloma cells with spleen cells from mice immunized with rat AFP. The monoclonal antibodies as well as horse anti-rat AFP were coupled via a dextran bridge to daunomycin. Both types of conjugates were tested in vitro and in vivo for their anti-tumor activity. They were equally cytotoxic to rat AH66 hepatoma cell line in culture. Rats challenged with hepatoma cells were treated with the conjugates either by intraperitonea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

1983
1983
1998
1998

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 17 publications
1
34
0
Order By: Relevance
“…The material included on the Sepharose 6B column was passed over a 3-ml protein A column at pH 8 Conjugates alone were assayed for toxicity by adding various concentrations of protein to cell monolayers at 370C for [16][17][18] hr. At the end of the incubation period, the medium was replaced with DME medium containing [3H]leucine.…”
mentioning
confidence: 99%
“…The material included on the Sepharose 6B column was passed over a 3-ml protein A column at pH 8 Conjugates alone were assayed for toxicity by adding various concentrations of protein to cell monolayers at 370C for [16][17][18] hr. At the end of the incubation period, the medium was replaced with DME medium containing [3H]leucine.…”
mentioning
confidence: 99%
“…This is the first study ever reported to use the system of antibody to human AFP: human AFPproducing tumour with very encouraging results. The utilization of monoclonal antibody to human AFP for conjugation with DM may be possible since a conjugate of DM with a monoclonal antibody to rat AFP proved to be as effective as the corresponding polyclonal antibody conjugate (Tsukada et al, 1982b;. The overall conclusion from the present study is that aAFP-PLGA-DM exhibits a potent antitumour activity toward a human AFP-producing neoplasm in nude mice by the homing effect of antibody.…”
Section: 14+006)mentioning
confidence: 52%
“…Recently, the targeting chemotherapy by polyclonal or monoclonal antibodies to tumour-associated antigens has been extensively studied (Latif et al, 1980;Embleton et al, 1981;Bernhard et al, 1983;Garnett et al, 1983). Similar approaches have been made utilizing purified antibody to rat AFP and anticancer drugs such as daunorubicin (DM) and mitomycin C (MMC) (Tsukada et al, 1982a;1982b;. Recently our-laboratory (Kato et al, 1983) developed a new method of conjugation of DM with antibody with a single thiol group-bearing PLGA derivative as intermediate drug carrier and the anti-rat AFP antibody-PLGA-DM conjugate prepared by this method showed a potent antitumour activity against the AFP-producing ascites hepatocellular carcinoma cells AH66 growing in DONRYU rats .…”
Section: 14+006)mentioning
confidence: 99%
See 1 more Smart Citation
“…ated processes by the nontarget cells, and (ii) selectively deliver the drug only to the target cells at relatively low plasma concentrations. Attempts have been made for selective delivery of cytotoxic agents exclusively to the neoplastic cells using various antibodies, liposomes, DNA and growth factors as carriers [3][4][5][6] with varying degrees of success.…”
Section: Introductionmentioning
confidence: 99%